2019
DOI: 10.3390/coatings9120818
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Properties, and Titanium Cutting Performance of AlTiN–Cu and AlTiN–Ni Coatings

Abstract: In this study, three kinds of coatings, AlTiN, AlTiN–Ni, and AlTiN–Cu were deposited via the cathodic arc evaporation method. The microstructure, mechanical properties, oxidation resistance, and cutting behavior of these coatings were then investigated. The incorporation of Cu(Ni) into AlTiN eliminated its columnar structure and led to an increase in the growth defects of its macroparticles. The addition of Cu and Ni decreased the hardness of the coatings, their elastic moduli, and their friction coefficients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…AlTiN contains smaller atomic radius of higher Al content than Ti content; therefore, it is dense and formed coarse grained with columnar structure. Yi et al 33 have also reported similar results. The high hardness of AlTiN is attributed to the solid solution hardening of the element Al which decreases the lattice constant of the coating.…”
Section: Resultssupporting
confidence: 53%
“…AlTiN contains smaller atomic radius of higher Al content than Ti content; therefore, it is dense and formed coarse grained with columnar structure. Yi et al 33 have also reported similar results. The high hardness of AlTiN is attributed to the solid solution hardening of the element Al which decreases the lattice constant of the coating.…”
Section: Resultssupporting
confidence: 53%
“…The reason for these discrepancies can be traced to different thermophysical properties of the coatings in this group. The thermal conduction of these materials, especially in the lower temperature, is much less than that of the coatings based on TiN, TiCN, or the carbide H10F itself [ 18 , 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the report, TiAlN-Cu coatings with about 1.3 at.% Cu can exhibit excellent mechanical properties and can demonstrate an excellent cutting performance. Yi et al also found [23] that the addition of Cu(~1.3 at.%) into the AlTiN coatings resulted in a decrease in its grain size and hardness, and their turning experiments showed that the additive Cu effectively decreased the turning force, thereby extending tool lifetimes at various cutting speeds. However, few studies have been reported on the effect of Cu addition into the quinary coating systems [24,25], especially for the deposition of nanocomposites with superhard coatings.…”
Section: Introductionmentioning
confidence: 99%